Identifikasi dan Respon Masyarakat terhadap Ancaman Terorisme di Kota Makassar - Sanusi, Arham Ichwardani (SIGn Journal of Social Science, 2024)
Terrorism is a complex global threat, and understanding community responses to this threat is crucial. This qualitative case study aims to explore in-depth the identification and responses of the Makassar City community to the threat of terrorism, particularly following the bombing in front of the Cathedral. Research data was obtained through in-depth interviews with residents, community leaders, religious figures, and security officials, as well as analysis of documents and media reports. The results show that the Makassar City community identifies terrorist group characteristics through factual knowledge and stereotypes. This identification process also involves analyzing the responses of certain groups to government policies and maintaining awareness of the potential for issue manipulation by political elites. Furthermore, the mass media plays a significant role in shaping public perceptions and responses. This research confirms that inaccurate identification can trigger stigmatization and discrimination. Community responses to government policies and local political dynamics become important indicators in identifying potential terrorist movements. In conclusion, community identification of and response to the threat of terrorism is a dynamic and multidimensional process requiring a comprehensive and participatory approach to prevention efforts.